2004
DOI: 10.1021/jp0301406
|View full text |Cite
|
Sign up to set email alerts
|

Probing Förster and Dexter Energy-Transfer Mechanisms in Fluorescent Conjugated Polymer Chemosensors

Abstract: Fluorescence quenching in solutions of a pendant-functionalized conjugated polymer chemosensor (ttp-PPETE) has been evaluated in the presence of a variety of transition metal cations, including Ni2+, Co2+, Cu2+, Fe2+, and Cr6+. Photophysical analysis of the emission quenching revealed a static quenching mechanism that demonstrated strong positive deviations from predicted linear behavior. The enhanced emission quenching mechanism was found to correlate closely with the relative loading of the cationic analytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
187
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(192 citation statements)
references
References 39 publications
4
187
0
1
Order By: Relevance
“…19,20 The modified Stern-Volmer plots are showed in Figure 3 and the corresponding quenching constants K a at different temperatures were given in Table 1. The decreasing trend of K a with increasing temperature suggested that the quenching is not initiated by dynamic collision but by the formation of a complex, that is to say, the quenching is a static process.…”
Section: Effect Of Qds On Bsa Fluorescencementioning
confidence: 99%
“…19,20 The modified Stern-Volmer plots are showed in Figure 3 and the corresponding quenching constants K a at different temperatures were given in Table 1. The decreasing trend of K a with increasing temperature suggested that the quenching is not initiated by dynamic collision but by the formation of a complex, that is to say, the quenching is a static process.…”
Section: Effect Of Qds On Bsa Fluorescencementioning
confidence: 99%
“…Second, the hippocampus contains the hippocampal fissure, where SPION may be detected before its uptake/distribution. We selected the contralateral somatosensory cortices (SSCs) as our ROI for analysis because it is distant from the ventricle and the air-surface interface of the trachea (Murphy et al, 2004;Li et al, 2005).…”
Section: Spion-sodn Report Endogenous Gene Transcript In Live Animalsmentioning
confidence: 99%
“…As is evident from Figure 5 and 6, an effective fluorescence quenching can be detected upon the addition of Cd 2þ , Zn 2þ , Fe 2þ , Mn 2þ , and Co 2þ ions at the ratio of 1:10, whereas there is a nearly-complete fluorescence quenching of Cu 2þ and Ni 2þ to the polymer, which can be attributed to the energy or electron-transfer between the polymer backbones and binding metal complexes in the conjugated polymer backbone. [10,15,18,20,75] According to Table 3, and Figure 6, the chiral polymer can still show fluorescence upon the addition of the Cd 2þ , Zn 2þ , Fe 2þ , Mn 2þ , and Co 2þ ions, even at a high concentration of 20:1 molar ratio, but the intensity of the fluorescence spectra of the Cu 2þ and Ni 2þ -chelating polymers is very weak. It was also found that there is no obvious difference between the emission wavelengths of all of the metal-polymer complexes and the metal-free polymer.…”
Section: Responsive Properties Of Transition-metal Ionsmentioning
confidence: 99%
“…Conjugated polymers incorporating molecular-recognition moieties can use the conjugated polymer's high sensitivity to external structural perturbations and to electron density changes within its main-chain backbone and at the same time they can interact and form complexes with transition-metal ions. [12][13][14][15][16][17][18][19] Sensitive detection methods employed for sensing metal ions involve the design of ''turn-on'' fluorescent chemosensors based on the photoinduced electron transfer and energymigration mechanism in the conjugated polymer backbone. [10,11,[20][21][22] Functional polymers bearing chiral moieties and the extended conjugated p-system have attracted considerable interest over the past decade.…”
Section: Introductionmentioning
confidence: 99%